Prevalence and related factors of caregiving burden among family caregivers of patients with mental illness in China - Deng, Ruibo; Wu, Yongming; Huang, Shuyun; He, Yuhang; Liu, Chenyu; Zhang, Ziyun; Wu, Kai; Fong, Lam Mei; Wu, Fengchun; Li, Hehua (Frontiers in Psychiatry, 2026)
BackgroundFamily caregivers are essential yet often overburdened in mental healthcare systems. However, the burden of Family caregivers in Mainland China remains limited. This study examines the prevalence of caregiving burden among family caregivers of individuals with mental illness in Mainland China and explores its association with personal and familial factors.MethodsEmploying a cross-sectional design, we recruited 400 family caregivers from the Affiliated Brain Hospital of Guangzhou Medical University and the Second Affiliated Hospital of Guangzhou Medical University in China. This study collected data using the Zarit Burden Interview (ZBI) and the Family Burden Scale of Disease (FBSD).ResultsThe prevalence of caregiving burden was 57.25%. Caregivers with burden reported higher levels of economic burden, greater disruptions in family activities and entertainment, increased family relationship tension, and worse physical and mental health among family members than those without burden. They also had longer caregiving durations, greater economic burden pressure due to the patient’s illness, and generally lacked co-caregivers compared to caregivers without burden. The impact of the patient’s illness on economic burden, family activities, family entertainment, and the physical and mental health of family members was positively associated with the occurrence of caregiving burden, while the presence of co-caregivers had a protective effect (OR < 1). ROC curve analysis further identified disruptions in family activities, family entertainment, and economic burden as significant predictors of caregiving burden (AUC > 0.70).ConclusionsCaregiving burden is strongly linked to economic burden, impaired family functioning, and the physical and mental health of family members, while co-caregiver support mitigates this burden. These findings highlight the need for comprehensive support strategies, including economic assistance and shared-caregiving models, to alleviate caregiver burden within the mental healthcare system.